The use of glucocorticoid in severe fever with thrombocytopenia syndrome: a retrospective cohort study - Chen, Yuzhang; Wang, Huan (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionSevere fever with thrombocytopenia syndrome (SFTS) is prevalent in East Asia. However, the use of glucocorticoids (GCs) in the treatment of SFTS remains controversial.MethodsIn this retrospective cohort study, we collected the data from patients with SFTS at Wuhan Union Hospital to evaluate the effect of GC therapy. Mortality and secondary infections were compared as outcomes. After searching public databases, we also included articles that examined GC use in patients with SFTS for meta-analysis.ResultsPatients treated with GC had higher fatality rates (21.1% vs. 11.9%, respectively; P=0.006) and a longer length of stay (10.6 ± 5.1 vs. 9.5 ± 4.2, respectively; P=0.033). In cohorts adjusted using propensity score matching and inverse probability of treatment weighting, no significant differences in fatality rates and length of stay were observed. A meta-analysis of 4243 SFTS patient revealed that those treated with GCs had significantly higher mortality (OR=3.46, 95% CI =2.12-5.64, P<0.00001) and secondary infection rate (OR=1.97, 95% CI=1.45-2.67, P<0.0001).DiscussionGC should be used cautiously when treating SFTS. No significant differences were identified in terms of mortality and secondary infection rates between patients with SFTS treated with or without GC.